Analysis of Administrator Officials' Perceptions of Priorities Core Values of the State Civil Apparatus - Biryanto (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2023)
Implementing the core values ​​of the State Civil Apparatus is needed to realize the transformation of a world-class government bureaucracy. As a new policy, these core values ​​give rise to various perceptions of the State Civil Apparatus. This study aims to determine the perceptions of administrator officials on the core values ​​of the State Civil Apparatus and the priority of implementing each of the core values ​​of the State Civil Apparatus on staff and officials. The approach used in this research is quantitative. The research respondents were administrator officials who attended Administrator Leadership Training within the Meranti Islands Regency Government in 2022. Before data collection, all respondents were given an explanation of material and interactive discussions related to the core values ​​of the State Civil Apparatus. Data collection methods using a questionnaire followed by interviews to clarify and reinforce research findings. Data analysis used the Wilcoxon test to determine the significance of the average difference in respondents' perceptions of ASN core values ​​priorities in the staff and official categories. The research results show that the respondents' perceptions of the priorities for implementing the core values ​​of the State Civil Apparatus for staff and officials had a significant difference on average on three values: service-oriented, adaptive, and collaborative. Accountability is the most priority value that must be implemented by all levels of the State Civil Apparatus in carrying out its duties and functions.